2006
DOI: 10.1080/09603100500426572
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear adjustment in the term structure of interest rates: a cointegration analysis in the non-linear STAR framework

Abstract: The term structure of interest rates in Japan is analysed by means of a cointegration test in a non-linear smooth transition autoregression (STAR) framework. The STAR approach tests for the null hypothesis with no cointegration against cointegration including a globally stationary process. The results of the STAR cointegration test, differing from the results of cointegration tests assuming linear adjustment, show that the long-run equilibrium relationship between long-term and short-term interest rates is sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…If ( , ) and (1, ) have a unit root, the cointegration relationship described above can be tested for the pre-specified cointegrating vector such as (1, − 1)′ by using unit root tests, including that of Dickey and Fuller (1979). However, the long run equilibrium relationship does not necessarily have an ex ante one-to-one proportional relationship (Maki 2006). Instead, the following long run relationship with a relaxed form can be estimated:…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…If ( , ) and (1, ) have a unit root, the cointegration relationship described above can be tested for the pre-specified cointegrating vector such as (1, − 1)′ by using unit root tests, including that of Dickey and Fuller (1979). However, the long run equilibrium relationship does not necessarily have an ex ante one-to-one proportional relationship (Maki 2006). Instead, the following long run relationship with a relaxed form can be estimated:…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the literature related to the EH, a group of studies has used spot and future prices (Dwyer et al 1996;Martens et al 1998;Tsay 1998) while another group of studies has used interest rates of different maturities (Anderson, 1997;Brüggemann and Lütkepohl, 2005;Enders and Granger, 1998;Maki, 2006;Musti and D'Ecclesia, 2008;Tsay, 1998). This study follows the latter group since the formulations of the EH in this study are derived in terms of spread and changes in interest rates.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Clarida et al (2006) found presence of nonlinearities and asymmetries in the term structure for Germany, Japan and US data. Kuo and Enders (2004) and Maki (2006) reported non-linear adjustment in the term structure of Japanese interest rates. These studies find that although there is a long run equilibrium relationship between short term and long-term interest rates, this adjustment process may be non-linear in some of the developed countries.…”
Section: Introductionmentioning
confidence: 99%